From Theory to Practice: The Role of Amanda Labarca in the Reception of Psychology in the Chilean School; [de la Teoría a la Práctica. el Rol de Amanda Labarca en la Recepción de la Psicología en la Escuela Chilena] - Letelier-Soto, A (Instituto Tecnologico y de Estudios Superiores de Monterrey, 2024)
The history of the relationship between psychology and education in Chile has been documented with emphasis on the period from 1850 to 1950. This research adds to these efforts and explores the contributions of Professor Amanda Labarca, particularly those orientations that prioritized the application of psychology over its conceptualization. To do this, various primary sources from the first half of the 20th century are used, with a focus on the text Nuevas Orientaciones de la Enseñanza (New Teaching Orientations). Additionally, reception studies are incorporated to understand the circulation of these proposals. The results highlight the importance of the text as a means of disseminating psychological ideas, directed towards the application of the psychological discipline within schools. Students and teachers are also identified as key actors and the target population of these psychological trends. Teaching methods, variables prioritized in the learning process, as well as the principles of the new school, which were attempted to be implemented first as proposals and later observed in the implementation of the Liceo Experimental Manuel de Salas, are highlighted. The findings invite further exploration of this transitional period in psychology to understand the practices that were well-received in the school environment, as well as to identify processes that could not be replicated. This reinforces the need to pay greater attention to women s proposals, from which direct links with psychology continue to be visible. © 2023. The Author(s).